Effect of Bacterial Infection on the Edibility of Aquatic Products: The Case of Crayfish (Procambarus clarkii) Infected With Citrobacter freundii - Huang, Xiaoli; Li, Minghao; Wang, Jincheng; Ji, Lili; Geng, Yi; Ou, Yangping; Yang, Shiyong; Yin, Lizi; Li, Liangyu; Chen, Defang (Frontiers in Microbiology, 2021)
As one of the world's important sources of protein, the quality and safety of aquatic products are threatened by bacterial diseases. This study investigated the possible effects of bacterial infection on the main edible part, the muscle, in the case of crayfish infected with Citrobacter freundii. The experimental infection and histopathological analysis confirmed that crayfish was sensitive to C. freundii and muscle was one of the target organs. The transcriptome results showed impaired intercellular junctions, down-regulation of actin expression and inhibition of metabolic pathways. Further, based on the transcriptomic results, we found that C. freundii might mainly affect muscle structure and nutrition. Subsequent validation experiments confirmed structural damage and nutrient loss in crayfish muscle infected with C. freundii. Besides, the spoilage tests showed that C. freundii did not accelerate muscle spoilage and the bacteria had a limited impact on food safety. Therefore, although C. freundii may not be a specific spoilage bacterium, it still affects the edible taste and nutritional value of crayfish muscle. The findings of this study might contribute to further research on C. freundii infection and provide a warning about the adverse effects of bacterial infection on aquatic products.